Thrombus aspiration in patients with ST-elevation myocardial infarction: results of a national registry of interventional cardiology - Pereira, H (2018)
BACKGROUND: We aimed to evaluate the impact of thrombus aspiration (TA) during primary percutaneous coronary intervention (P-PCI) in 'real-world' settings. METHODS: We performed a retrospective study, using data from the National Registry of Interventional Cardiology (RNCI 2006-2012, Portugal) with ST-elevation myocardial infarction (STEMI) patients treated with P-PCI. The primary outcome, in-hospital mortality, was analysed through adjusted odds ratio (aOR) and 95% confidence intervals (95%CI). RESULTS: We assessed data for 9458 STEMI patients that undergone P-PCI (35% treated with TA). The risk of in-hospital mortality with TA (aOR 0.93, 95%CI:0.54-1.60) was not significantly decreased. After matching patients through the propensity score, TA reduced significantly the risk of in-hospital mortality (OR 0.58, 95%CI:0.35-0.98; 3500 patients). CONCLUSIONS: The whole cohort data does not support the routine use of TA in P-PCI, but the results of the propensity-score matched cohort suggests that the use of selective TA may improve the short-term risks of STEMI..